As locuções conjuntivas dado que, desde que e uma vez que no PB: condicionalidade-causalidade - Cavaguti, Ana Paula (2013)
In this research, we propose the synchronic study of adverbial clauses initiated by conjunctions dado que, desde que and uma vez que in written Brazilian Portuguese. Considering that these conjunctions may express causality and conditionality, the distinction between the interpretation of causal clauses and conditional clauses is not only a result of syntactic features but also of semantic and pragmatic ones. The analysis is based on the Functionalist Theory, in the terms of Dik (1989), Hengeveld (1998), Hengeveld and Mackenzie (2008), Sweetser (1990), among others, and this study provides, through a detailed description of these conjuctions at the discourse level, characteristics of dado que, desde que and uma vez que in their effective use. The corpus of this research is composed by written texts, which were collected at the Corpus do Português, available at: http://www.corpusdoportugues.org. The features considered in this analysis were: (i) the order of the causal and the conditional clauses in relation to the main clause, (ii) the verbal tenses correlations, (iii) the semantic parameters (type of entity; factuality; presupposition and time dependence) proposed by Hengeveld (1998), (iv) levels and layers of analysis, according to Hengeveld and Mackenzie (2008), and (v) domains of use of Sweetser (1990). This research aims at showing how a natural language user 'acts', so that his/her verbal interaction is successful in face of his/her communicative intentions. This study also provides linguistic subsidies for the automatic treatment of language.